Risk factor analysis among patients with stroke: a cross sectional study at a tertiary care hospital - B., Rajiv Kumar; Kishan, U.; Kumar N., Arun (International Journal of Advances in Medicine, 2018)
Background: Study of risk factors of stroke is very important in different settings to confirm their existence and to take necessary steps to prevent them especially in elderly so that incidence of stroke can be brought down. The objective of the present study is to perform the risk factor analysis among patients with stroke. Methods: A hospital based cross sectional study was carried out at a tertiary care hospital from June 2015 to March 2016. A total of 40 patients diagnosed with stroke were included in the present study. Detailed information and all necessary investigations were carried out. Risk factor analysis was done, and categorization was done for certain risk factors. Results: The predominant age group was 6-60 years. The age ranged from 1 month to 67 years. The Male: Female ratio was 14:9. The common etiologies were congenital, post infective and intracranial bleed in 26.1% (n=6) each. Favourable outcome was seen in 82.6% of cases. The failure rate was 17.4%. Most no of cases with favourable outcome was seen in 6-60 years age group, whereas >60 years age group had the most no of cases with poor outcome. The overall mortality rate was 21.6% (n=5). Wound related complication was seen in 1 patient (4.3%). Two (8.7%) patients required VP shunt post ETV. The cause of mortality was aspiration pneumonitis in 3 cases, CSF metastasis and wound infection in 1 cases each. Conclusions: The leading cause as well as risk factor for stroke was found to be hypertension followed by alcohol and smoking.